ANALISIS CAPITAL BUDGETING SEBAGAI PENDEKATAN PENGAMBILAN KEPUTUSAN INVESTASI PEMBANGUNAN INTEGRATED DRY BULK TERMINAL PELABUHAN PULAI BAAI, BENGKULU (STUDI KASUS PT PELABUHAN INDONESIA II) - Oscar Herminto Hasmoro; Edi Wahyu Wibowo; Aloysius Harry Mukti (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2021)
Accelerating infrastructure development is one of the Government's programs in order to promote sustainable economic growth, especially for port development that have function as an economic gate and as a logistic chain supply that able to give many positive effect for growth of a country. Besides that a development port able to give economic benefit for PT. Pelindo II as an investor. Prudent investment in fixed assets needs to be a major concern. This study aims to determine the feasibility analysis of investment and financial aspects of the planned dry bulk terminal development project using the capital budgeting method, the method that are PP (Payback Periode) = 7 year and 1 Month, NPV (Net Present Value) = Rp 391.341.133,01 , Internal Rate of Return (IRR) = 17,1 % dan Profitability Indexs (PI) = 1.70. bisides that also consider to Legal aspec, Marketing aspek and Technical & Operational aspec.This research method is a case study with the object of research at PT. Pelabuhan Indonesia II Bengkulu Branch. The results show that the investment decision is feasible to proceed to the development stage by considering the financial aspects consisting of payback period (PP) = , net present value (NPV) =, internal rate of return (IRR) = and profitability index (PI) = . The sensitivity test with the risk assessment of the pessimistic scenarios shows that it is still feasible to invest in continuing into the development phase.